The relative impact of smoking, alcohol use and drug use on general sickness absence among Norwegian employees - Ingeborg Lund; Inger Synnøve Moan; Hilde Marie Erøy Edvardsen (BMC, 2019)
Abstract Background It is well documented that tobacco, alcohol and drug use can be detrimental to health. However, little is known about the relative impact of these factors on sickness absence, and whether the association between use of these substances and sickness absence is different for women and men. The aim of this study was to examine the association between tobacco-, alcohol- and drug use, as well as polydrug use, and sickness absence among Norwegian employees. Methods During 2011-2014, 1911 employees in Norway completed a questionnaire about their tobacco, alcohol and drug use habits, their total number of sickness absences during the last 12 months, and the length (no. of days) of their last sick leave. Samples of oral fluid were analysed for illegal and medicinal drugs. Results Daily smoking and current use of medical drugs were significantly associated with sickness absence. Employees who were daily smokers also had an increased likelihood of having long and frequent sickness absence. Use of snus (Swedish moist snuff), binge drinking, current use of illegal drugs and polydrug use were not significantly associated with sickness absence. Women and young participants were more likely to report having had sickness absence the past 12 months. However, the associations between daily smoking and medical drug use and sickness absence, respectively, were only statistically significant for men. Conclusion According to this study, daily smoking and use of medical drugs are the substance use habits most closely associated with sickness absence. Implications for future research are discussed.